Monster - Roehrig, Paul; Pring, Ben (Ascent Audio, 2021)
Monster explains how we can responsibly engage with technology, and avoid its darker tendencies, while accepting its necessary gifts. The authors, insiders at one of the world's largest tech consulting firms, give a unique take on: - The addictive nature of tech and how to fight it - The growing backlash against big tech-where it's right and what it misses - Crucial steps for taming technology's role in your life and in your organization-without becoming a modern Luddite Written for managers, leaders, and employees at companies of all sizes and in all industries, Monster will help you understand and take control of technology's powerful role in your life and your organization.